1993
DOI: 10.1042/bj2930243
|View full text |Cite
|
Sign up to set email alerts
|

Dystrophin is phosphorylated by endogenous protein kinases

Abstract: Dystrophin, the protein coded by the gene missing in Duchenne muscular dystrophy, is assumed to be a component of the membrane cytoskeleton of skeletal muscle. Like other cytoskeletal proteins in different cell types, dystrophin bound to sarcolemma membranes was found to be phosphorylated by endogenous protein kinases. The phosphorylation of dystrophin was activated by cyclic AMP, cyclic GMP, calcium and calmodulin, and was inhibited by cyclic AMP-dependent protein kinase peptide inhibitor, mastoparan and hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 39 publications
2
30
0
Order By: Relevance
“…Furthermore, like other ecto-ATPases (33,45,46), the ATPase activity of dystrophinDAPs preparations was not inhibited by inhibitors of ion-translocating ATPases such as thapsigargin, cyclopiazonic acid, and vanadate (data not shown). It appears likely that the relatively low specific activity is because of the presence of digitonin, used to purified the DAP complex (22,23). Indeed, it has been demonstrated that detergents inhibit the activity of other ectoATPases (31,33).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, like other ecto-ATPases (33,45,46), the ATPase activity of dystrophinDAPs preparations was not inhibited by inhibitors of ion-translocating ATPases such as thapsigargin, cyclopiazonic acid, and vanadate (data not shown). It appears likely that the relatively low specific activity is because of the presence of digitonin, used to purified the DAP complex (22,23). Indeed, it has been demonstrated that detergents inhibit the activity of other ectoATPases (31,33).…”
Section: Resultsmentioning
confidence: 99%
“…isolated as described previously (22). The purification of the dystrophinDAPs complex was performed according to the digitonin, 0.5 M NaCl, wheat germ agglutinin protocol of Ervasti et al (23), as described previously (24), with the only difference being that the dystrophinDAPs purification was terminated after the DEAE-cellulose column chromatography.…”
mentioning
confidence: 99%
“…Triads were prepared using the method of Mitchell et al (1983), with slight modifications (Luise et al 1993). Production of these monoclonal antibodies was carried out by immunizing Balb/C mice (Charles River, Italy) with the triad membrane fraction, according to established procedures.…”
Section: Serca Antibodiesmentioning
confidence: 99%
“…Two Ca 2+ -calmodulin binding sites at the N-terminal domain of dystrophin appear to control 376 both polymerization [73] and interaction with F-actin [74]. Dystrophin is phosphorylated by endogenous and exogenous protein kinase [75,76] and phosphorylation modulates its actin-binding activity [77].…”
Section: Functional Roles Associated With the Dystrophin-daps Complexmentioning
confidence: 99%